(untitled) (Journal of Forest and Livelihood, 2024)
The author contends that the prevailing community forestry policy and legislations can be implemented to solve problems of Terai forest management. Based on on-going experiences in the Chure and inner Terai region in eastern Nepal, he puts forward an approach that integrates community forestry with natural resource management involving various stakeholder groups. The conclusion is that before attempting any change in legislation, more experiences may be gained by sincere efforts to implement community forestry in the Terai region of Nepal.